The Practice and Performance of Katajjaq: Culture, Identity and Resistance - Singh, Raj Shobha (2022)
Katajjaq, or vocal games, has a long history among the Inuit of Canada. Practiced almost exclusively by women, katajjaq is a playful competition between two or more partners who face each other and exchange sound motifs; one is leading, while the other repeats the same motifs. The first person unable to maintain the rhythm, tempo, or breathing pattern will laugh, indicating that they have lost the game. An oral tradition, katajjaq continues to be a popular practice amongst Inuit. In addition, katajjaq has recently moved from the realm of game to becoming an integral component of Inuit music. Katajjaq's shift from game to music is also accompanied by an increase in male participation. Notably, Nelson Tagoona combines katajjaq with beatboxing to create a genre he calls "throat boxing." The primary purpose of this dissertation is to examine katajjaq. I explore how it is understood, practiced and sometimes recontextualized by numerous Inuit culture bearers as well as how it has been studied and portrayed by ethnomusicologists. In this way I scrutinize research gaps in ethnomusicological investigations about katajjaq and point to how Inuit epistemology and ontology provide culturally appropriate ways of understanding katajjaq. For instance, the complexity and significance of the imaq-nuna-sila (water-land-sky) relationship in Inuit epistemology as well as Inuit Qaujimajatuqangit (IQ), or the guiding principles of Inuit life and ways of knowing and being provide a richer understanding of the role of katajjaq in Inuit life. The secondary purpose of this dissertation is to present the musical life and creative choices of Nelson Tagoona and trace how he contributes new meaning to katajjaq. Some of my research questions include: What creative and cultural choices are made when a living cultural tradition is combined with a contemporary popular practice? How does Nelson Tagoona negotiate and mediate tradition and innovation? How has the inclusion of hip hop culture with katajjaq affected the meaning of throat singing? By ...